Individual Psychosocial Resilience, Neighborhood Context, and Cardiovascular Health in Black Adults: A Multilevel Investigation From the Morehouse-Emory Cardiovascular Center for Health Equity Study. Issue 10 (October 2020) - Kim, Jeong Hwan; Islam, Shabatun J.; Topel, Matthew L.; Ko, Yi-An; Mujahid, Mahasin S.; Vaccarino, Viola; Liu, Chang; Sims, Mario; Mubasher, Mohamed; Searles, Charles D.; Dunbar, Sandra B.; Pemu, Priscilla; et al.
Abstract : Background: Despite well-documented cardiovascular disparities between racial groups, within-race determinants of cardiovascular health among Black adults remain understudied. Factors promoting cardiovascular resilience among Black adults in particular warrant further investigation. Our objective was to examine whether individual psychosocial resilience and neighborhood-level cardiovascular resilience were associated with better cardiovascular health in Black adults, measured utilizing Life's Simple 7 (LS7) scores. Methods: We assessed LS7 scores in 389 Black adults (mean age, 53±10 years; 39% men) living in Atlanta, Georgia. A composite score of individual psychosocial resilience was created by assessing environmental mastery, purpose in life, optimism, resilient coping, and depressive symptoms. Neighborhood-level cardiovascular resilience was separately determined by the census tract-level rates of cardiovascular mortality/morbidity events. Generalized linear mixed regression models were used to examine the association between individual psychosocial resilience, neighborhood cardiovascular resilience, and LS7 scores. Results: Higher individual psychosocial resilience was significantly associated with higher LS7 (β=0.38 [0.16–0.59] per 1 SD) after adjustment for sociodemographic factors. Similarly, higher neighborhood-level cardiovascular resilience was significantly associated with higher LS7 (β=0.23 [0.02–0.45] per 1 SD). When jointly examined, high individual psychosocial resilience (>median) was independently associated with higher LS7 (β=0.73 [0.31–1.17]), whereas living in high-resilience neighborhoods (>median) was not. The largest difference in LS7 score was between those with high and low psychosocial resilience living in low-resilience neighborhoods (8.38 [7.90–8.86] versus 7.42 [7.04–7.79]). Conclusions: Individual psychosocial resilience in Black adults is associated with better cardiovascular health. Abstract : Supplemental Digital Content is available in the text.